Motor memory consolidation in children: The role of awareness and sleep on offline general and sequence-specific learning - Iranmanesh Hamideh; Kakhki Alireza Saberi; Taheri Hamidreza; Shea Charles H. (Sciendo, 2022)
Study aim: The purpose of this study was to investigate the role of sleep and awareness on consolidation of general and Sequence-Specific learning in children.